2018
DOI: 10.1097/md.0000000000009755
|View full text |Cite
|
Sign up to set email alerts
|

What may cause fetus loss from acute pancreatitis in pregnancy

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
41
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(48 citation statements)
references
References 31 publications
6
41
1
Order By: Relevance
“…Alcoholism, drug abuse, history of receiving endoscopic retrograde cholangiopancreatography and abdominal surgery were categorized as 'other causes' [19]. Fetal loss included spontaneous or artificially abortion, intrauterine fetal death and induced labor [2].…”
Section: Diagnosis and Definitionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Alcoholism, drug abuse, history of receiving endoscopic retrograde cholangiopancreatography and abdominal surgery were categorized as 'other causes' [19]. Fetal loss included spontaneous or artificially abortion, intrauterine fetal death and induced labor [2].…”
Section: Diagnosis and Definitionsmentioning
confidence: 99%
“…It accounts for approximately 1/1000 to 1/12,000 of pregnancies [1]. Data from recent Chinese studies indicated higher incidence up to 1.37% and 2.27%, respectively [2,3]. APIP is more dangerous to the fetus than to the mother.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that risk of fetal loss is more in cases of acute pancreatitis in pregnancy due to hypertriglyceridemia than other causes of pancreatitis [6]. So these cases need special attention and monitoring for mother and fetus and timely intervention to void maternal and fetal complications.…”
Section: Managing Principlesmentioning
confidence: 99%
“…This may lead to preeclampsia or pancreatitis. Though rare, hypertriglyceridemia induced pancreatitis may lead to fatal maternal and fetal complications, even maternal death [4][5][6]. Acute complications of electrolyte imbalance, acute respiratory distress syndrome, disseminated intravascular coagulation and preterm labour may worsen the clinical situation.…”
Section: Introductionmentioning
confidence: 99%
“…If AP is not correctly diagnosed and treated, it can lead to pancreatic necrosis, abscess, and multiple organ dysfunction and subsequently maternal and fetal morbidity and mortality. [7][8][9] Despite the issues, there are no guidelines currently available for AP diagnosis and management in pregnant women. In addition, a gallstone disease (acute cholecystitis, choledocholithiasis, cholangitis, or gallstone pancreatitis) is the most common cause of maternal hospitalization in the first year after delivery.…”
Section: Introductionmentioning
confidence: 99%